Bringing Industry Back to Conferences, and Paying for Results. - Patterson, David; Bugayenko, Yegor (Communications of the ACM, 2020)
The article presents blog postings on the topics of scientific papers at conferences and the problem of monitoring and paying for productivity from telecommuting computer programmers.